Secondary Organic Aerosol Formation from Ambient Air at an Urban Site in Beijing: Effects of OH Exposure and Precursor Concentrations - Liu, Jun; Chu, Biwu; Chen, Tianzeng; Liu, Changgeng; Wang, Ling; Bao, Xiaolei; He, Hong (Environmental science & technology, 2018)
Secondary organic aerosol (SOA) is an important component of atmospheric fine particles (PM2.5), while the key factors controlling SOA formation in ambient air remain poorly understood. In this work, the SOA formation in Beijing urban ambient air was investigated using an oxidation flow reactor (OFR) with high concentrations of OH radicals. The SOA formation potential increased significantly with the increase of ambient PM2.5 concentration during the observation. The optimum ambient exposure time, which is the aging time equivalent to atmospheric oxidation (with similar OH exposure) associated with the peak SOA formation, varied between 2 and 4 days in this study. The OA enhancement in this study was much higher than that of developed countries under different environmental conditions. The higher OA enhancement is probably due to the higher concentrations of volatile organic compounds (VOCs) in the urban air of Beijing. This might also have occurred because fragmentation did not dominate in the oxidation of OA, and did not result in negative OA enhancement on highly polluted days compared to relatively clean days with similar exposure time. These results suggested that under typical ambient conditions, high concentrations of VOC precursors might contribute to sustained organic aerosol growth and long duration haze events in Beijing.